2007
DOI: 10.1007/s12134-007-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Threat and Expressions of Prejudice Toward the New Minorities of Western Europe

Abstract: This article presents a group position model of prejudice and a set of individual-level theoretical approaches to explain prejudice toward immigrants, who are a relatively new minority group in Western Europe. It specifically tests the effects of the perceived threat posed by the new minorities to the dominant group position of the citizens in the European nation-states. Threat is measured both as individuals' perceptions of threat over economic and sociocultural resources and as contextual factors. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous research suggests that feelings of realistic threat emerge when people start associating immigrants with competition over scarce resources and with making neighborhoods less safe (Stephan & Renfro, 2002;Stephan, Ybarra, & Bachman, 1999), which in turn fuels increased hostility toward immigrants and minority groups (Canetti, Halperin, Hobfoll, Shapira, & Hirsch-Hoefler, 2009;Huddy, Feldman, & Weber, 2007;Sari, 2007). In the present research program, we sought to extend previous work on the effects of realistic threats by focusing on tolerance of ideological groups rather than prejudice or intolerance of minority groups per se.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that feelings of realistic threat emerge when people start associating immigrants with competition over scarce resources and with making neighborhoods less safe (Stephan & Renfro, 2002;Stephan, Ybarra, & Bachman, 1999), which in turn fuels increased hostility toward immigrants and minority groups (Canetti, Halperin, Hobfoll, Shapira, & Hirsch-Hoefler, 2009;Huddy, Feldman, & Weber, 2007;Sari, 2007). In the present research program, we sought to extend previous work on the effects of realistic threats by focusing on tolerance of ideological groups rather than prejudice or intolerance of minority groups per se.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reached the conclusion that a large regional immigrant population increased intolerant attitudes (Schlueter and Wagner, 2008;Meuleman, Davidov and Billiet, 2009;Gorodzeisky and Semyonov, 2009), for example support for excluding non-European migrants from social rights. However, several other studies reached the opposite conclusion: that size of minority population does not correlate with levels of prejudice, either for minorities generally (Sari, 2007;Herreros and Criado, 2009) or specific minority groups such as Muslims (Strabac and Listhaug, 2008b) or Jews (Bergmann, 2008). The survey data available from the EVS were also inconclusive.…”
Section: Evidence On Significance Of Out-group Size Is Inconclusivementioning
confidence: 96%
“…Several studies indicated that greater perception of cultural or economic threat is associated with more intolerant attitudes. McLaren (2003) concluded that perceived threat is a strong predictor of willingness to expel migrants and treat them harshly, while Sari (2007) found that people became more prejudiced as perceived threat increased. Ramos et al (2006) showed that perceptions of economic threat were the best predictors of opposition to immigration by people of 'another race or ethnic group', with threat to cultural identity being an important predictor as well.…”
Section: Strong Associations For Contact and Perception Of Threatmentioning
confidence: 99%
“…People under terrorism threat vote more for right wing parties (Getmansky, & Zeitzoff, 2014). Threat perception is also related with prejudice levels (Sari, 2007).…”
Section: The Political Psychology Of Threat Perceptionsmentioning
confidence: 99%